Attention Economy: Smartphone dan Media Sosial Candu Manusia Modern? - Siti Reni; Masduki Asbari; Mohamad Biazt Ramadhan (Literaksi: Jurnal Manajemen Pendidikan, 2024)
The aim of this study is to find out whether technology can make people addicted to smartphones or social media in this day and age. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Kamino YouTube Channel entitled "Attention Economy: How Does Technology Make Us Addicted to Cell Phones and Social Media?" explained by Kamino and Gloria Mark. The results of this study explain that the world continues to change, in the past when people wanted to find out something, people had to search and come to the place they needed it, but in modern technology like today, this can be easily obtained without leaving the place. Technology in the Modern era makes it easy to obtain information, and can improve relationships, but unfortunately reduces habits that were usually carried out by humans in the pre-Modern era. This research began with the emergence of technology such as smartphones which can change everyone's perception. Technology can change a person's perspective on living life. This change in reality is happening and developing very quickly in society, one of which is in the tertiary environment.